Joint Programme on Gender Transformative Approaches for Food Security and Nutrition - CGIAR Gender Equality Initiative (CGIAR Initiative on Gender Equality, 2023)
During the launch of the ‘Guidelines for measuring gender transformative change in the context of food security, nutrition and sustainable agriculture’, a dialogue panel between a representative of the Rome-based Agencies and one from the ONE CGIAR system focused on the opportunities and challenges of assessing normative constraints to gender equality in agrifood systems.